Knowledge and attitude of surgical patients and their families toward anesthesia - Wang, Jie; Wang, Shuai; Zeng, Ruifeng (Frontiers in Medicine, 2024)
Introduction Anesthesia plays a critical role in modern surgical procedures by ensuring patient pain management and safety. This study aimed to investigate the knowledge and attitude of surgical patients and their families toward anesthesia. Methods This prospective, cross-sectional study included patients and their families in Wenzhou, China. Data collection and the measurement of knowledge and attitude scores were administered using a self-administered questionnaire. Results 503 participants (69.98% patients, 30.02% families) were included. The mean knowledge and attitude scores were 7.93 ± 6.11 (possible range: 0–26), and 32.64 ± 2.59 (possible range: 8–40), respectively, indicating an inadequate knowledge and positive attitude. Moreover, a multivariable logistic regression analysis showed that age [odd ratio (OR) = 0.394, p = 0.018], residence (OR = 0.424, p = 0.002), household income per month (OR = 0.297 0.380, p < 0.05), gender (OR = 1.680, p = 0.017), education (OR = 2.891, p = 0.017), and experienced anesthesia (OR = 4.405, p = 0.001) were independently associated with knowledge score. Additionally, knowledge score (OR = 1.096, p < 0.001), relationship with the patient (OR = 1.902, p = 0.009), and household income per month (OR = 0.545, p < 0.031) were independently associated with attitude score. Discussion In conclusion, surgical patients and their families in Wenzhou, China had inadequate knowledge while positive attitude towards anesthesia, which might be influenced by their sociodemographic characteristics, including age, gender, residence, education, household income, relationship with patient, and experienced anesthesia. These findings emphasize the necessity of customized educational programs aimed at improving anesthesia knowledge and attitudes of patients and their families, especially among those with older age and lower socioeconomic status.